If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 8 = 12n + -1 Reorder the terms: 8 + 3n = 12n + -1 Reorder the terms: 8 + 3n = -1 + 12n Solving 8 + 3n = -1 + 12n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-12n' to each side of the equation. 8 + 3n + -12n = -1 + 12n + -12n Combine like terms: 3n + -12n = -9n 8 + -9n = -1 + 12n + -12n Combine like terms: 12n + -12n = 0 8 + -9n = -1 + 0 8 + -9n = -1 Add '-8' to each side of the equation. 8 + -8 + -9n = -1 + -8 Combine like terms: 8 + -8 = 0 0 + -9n = -1 + -8 -9n = -1 + -8 Combine like terms: -1 + -8 = -9 -9n = -9 Divide each side by '-9'. n = 1 Simplifying n = 1
| 4x+12x=96 | | 5t^2+9t=15 | | 18(5x+2)=2x | | -9x-20=-182 | | 3s^2=10s | | 8n=-3 | | -80=4+7x | | 6x+18=29-10x | | b^2+8b+16=0 | | -80=4*7x | | 8x+16=36-11x | | F^2+2f-8=0 | | 18-x=-9 | | 2x-3(2x-8)=4(3x-8)+8x | | 6x+18=36-11x | | x-16x=-64 | | 2x+3=180 | | (7g+3)(2g-1)=0 | | 8x+5y=29 | | x^2+11x=180 | | 5x^2+15x-25=0 | | 3y-8=12y+10 | | 4x-3(2x+1)=3+2(3x-11) | | 3(4x-4)-2x=8x-25 | | 5(3+x)-2=17 | | 11b^2=-7 | | 5n^2=n+48 | | 10x^2+23x=42 | | -19p=-19 | | 18a^2-8=0 | | 3r^2-10r=48 | | 3x^2-6x=24 |